2011
DOI: 10.1038/cddis.2011.111
|View full text |Cite
|
Sign up to set email alerts
|

TNF-induced necroptosis in L929 cells is tightly regulated by multiple TNFR1 complex I and II members

Abstract: TNF receptor 1 signaling induces NF-κB activation and necroptosis in L929 cells. We previously reported that cellular inhibitor of apoptosis protein-mediated receptor-interacting protein 1 (RIP1) ubiquitination acts as a cytoprotective mechanism, whereas knockdown of cylindromatosis, a RIP1-deubiquitinating enzyme, protects against tumor necrosis factor (TNF)-induced necroptosis. We report here that RIP1 is a crucial mediator of canonical NF-κB activation in L929 cells, therefore questioning the relative cytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
200
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(231 citation statements)
references
References 41 publications
27
200
2
2
Order By: Relevance
“…To determine the exact function of FADD in necrosome formation in relation to MKRN1, we first depleted FADD in L929 and HT-29 cells. Consistent with a previous report 44 , knockdown of FADD significantly induced necroptosis in both cell types ( Fig. 5e; Supplementary Fig.…”
Section: Fadd Stabilization Upon Mkrn1 Depletion Prevents Necroptosissupporting
confidence: 93%
“…To determine the exact function of FADD in necrosome formation in relation to MKRN1, we first depleted FADD in L929 and HT-29 cells. Consistent with a previous report 44 , knockdown of FADD significantly induced necroptosis in both cell types ( Fig. 5e; Supplementary Fig.…”
Section: Fadd Stabilization Upon Mkrn1 Depletion Prevents Necroptosissupporting
confidence: 93%
“…A study using L929 cells with FADD knockdown by shRNA showed FADD depletion induced necroptosis ( Fig. 2F) (90). We also recently reported that siRNA-or shRNA-mediated knockdown of FADD in L929 and HT-29 cells resulted in an increase in RIP1-RIP3 necrosome formation and necroptosis in the presence of caspase inhibitor, whereas FADD overexpression in L929 cells delayed RIP1-RIP3 necrosome formation and necroptosis (Fig.…”
Section: The Roles Of Fadd On Apoptosis and Necroptosis In Vitro And supporting
confidence: 60%
“…As a critical role of FADD in caspase-8 activation, FADD deficiency is thought to lead to necroptosis by inhibiting caspase-8 function. Supporting this idea, FADD deficiency abrogated caspase-8 activity and resulted in necroptosis (90). However, FADD's functions on various stimuli-induced necroptosis are contradictory; it seems to be dependent of stimuli.…”
Section: Proposed Mechanisms By Which Fadd Regulates Necroptosis In Amentioning
confidence: 94%
See 1 more Smart Citation
“…This was evident when we used the L-929 clones. Inhibiting caspase-3 or caspase-8 in the cells that were dying after only 3 h of incubation with Tag7-Hsp70 complex led to their death after 20 h. Based on recent publications, caspase-8-dependent cleavage of the RIP1 kinase is considered to play the main role in inhibiting necroptosis (30). It has been shown that caspase-3 cleaves RIP1 at multiple sites in vitro but is incapable of cleaving it in vivo (21).…”
Section: Discussionmentioning
confidence: 99%